A method for preparing a colored oxide film layer for improving corrosion resistance of stainless steel
Patent Information
- Application Number
- CN202611056173.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-30
AI Technical Summary
现有硬膜处理技术主要包括化学浸泡封闭(如含铬酸和钼酸盐的封孔液浸渍)和简单电解坚膜,但化学浸泡封闭仅依赖物理吸附和化学沉积填充孔隙,膜层主体结构未发生致密化转变;简单电解坚膜通常与着色工序使用相同或相似镀液,导致最终膜层的耐腐蚀性能提升有限,但是在高湿度、盐雾或紫外线环境下长期稳定性不足
[0034]本发明克服了现有不锈钢表面处理技术在低成本基材表面形成高耐蚀性、高耐久性、高颜色重现性的彩色氧化膜层方面存在的不足,能够在奥氏体、铁素体、马氏体等多种类别不锈钢表面通过系统性电化学工艺形成致密彩色干涉氧化膜层,兼顾批量化低成本生产、颜色可控性和耐候耐久性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of stainless steel surface treatment technology, specifically relating to a method for preparing a colored oxide film layer to improve the corrosion resistance of stainless steel. Background Technology
[0002] Stainless steel is widely used in building curtain walls, appliance panels, rail vehicles, and kitchen and bathroom fixtures due to its excellent corrosion resistance, mechanical properties, and decorative appeal. The corrosion resistance of stainless steel primarily relies on the chromium-rich oxide passivation film that forms on its surface. This film, typically composed of Cr₂O₃ and small amounts of Fe₂O₃ and NiO, is only a few nanometers to tens of nanometers thick, yet possesses extremely high chemical stability, effectively preventing contact between corrosive media and the substrate. However, differences in alloy composition and microstructure among different types of stainless steel lead to significant variations in the quality and stability of their surface passivation films.
[0003] Based on metallographic structure, stainless steel is mainly classified into austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, duplex stainless steel, and precipitation-hardening stainless steel. Among them, austenitic stainless steel (such as the 200 series and 300 series) has a face-centered cubic crystal structure, contains high levels of chromium and nickel, and its surface passivation film is dense and stable, exhibiting the best corrosion resistance, but its material cost is relatively high. Ferritic stainless steel (such as the 400 series) has a body-centered cubic crystal structure, mainly containing chromium and almost no nickel; its surface passivation film has lower integrity and stability than austenitic stainless steel, and its corrosion resistance is moderate. Martensitic stainless steel, although it can achieve high strength through heat treatment, has a relatively low chromium content and is prone to forming chromium-depleted zones during heat treatment, resulting in poor corrosion resistance. In practical applications, the price of high-corrosion-resistant stainless steel is significantly higher than that of low-corrosion-resistant types, making it difficult to use high-corrosion-resistant materials in many cost-sensitive applications. Therefore, how to achieve a corrosion resistance level comparable to high-corrosion-resistant stainless steel through surface treatment technology on low-corrosion-resistant stainless steel, while simultaneously imparting good decorative properties, has become an important technical requirement in the field of stainless steel surface treatment.
[0004] In order to improve the surface corrosion resistance and decorative properties of stainless steel without increasing the cost of the base material, the industry has developed a variety of surface treatment technologies, mainly including physical vapor deposition (PVD), organic coating, electroplating, chemical oxidation and electrochemical coloring.
[0005] Physical vapor deposition (PVD) technology deposits a ceramic coating (such as TiN or CrN) with a thickness of 0.1–5 μm onto the surface of stainless steel by sputtering or evaporating a metal target (such as Ti, Zr, or Cr) in a vacuum environment. This technology can achieve high hardness (1500–2500 HV) and rich metallic colors (gold, rose gold, black, blue, etc.), but it requires large equipment investment and has high operating costs, making it unsuitable for mass production of large-area plates at low cost. Furthermore, the film layer is extremely thin, making it prone to thinning or even peeling under scratches from sharp objects or long-term abrasive wear, and it also has poor coverage uniformity for complex shapes or internal cavity structures.
[0006] Organic coating processes involve applying a colored transparent coating, varnish, or epoxy resin to the surface of stainless steel. While simple and cost-effective, organic coatings are prone to aging, chalking, and peeling under ultraviolet light, temperature cycling, and humidity. Once the coating peels off, the underlying metal is exposed, creating localized corrosion cells that accelerate substrate corrosion. Furthermore, the coating obscures the metallic texture of the stainless steel, limiting its decorative effect.
[0007] Electroplating processes (such as chromium plating and nickel plating) are mature technologies with low costs, but electroplating processes containing hexavalent chromium are subject to strict environmental regulations; moreover, the coating and the substrate are physically covered, and the bonding force is limited, and the pores in the coating may cause corrosion of the underlying substrate.
[0008] Chemical oxidation and electrochemical coloring techniques are important methods for colorizing stainless steel surfaces. Among them, the INCO method and its derivative processes involve immersing stainless steel in a hot chromic acid-sulfuric acid mixed solution (typical formulation: CrO3 240–300 g / L, H2SO4 450–500 g / L, temperature 80–90℃). Color is generated by controlling the oxide film thickness and utilizing the optical interference effect. The oxide film layer produced by this technique is chemically bonded to the substrate, not physically covered, and can exhibit interference colors such as blue, golden yellow, red, magenta, and emerald green. It displays an iridescent effect depending on the viewing angle, possessing unique aesthetic value.
[0009] However, the colored oxide films obtained by the existing INCO method are relatively soft, contain micropores, and have inherently insufficient wear resistance and corrosion resistance. They must rely on subsequent hard coating treatments (sealing or hardening) before they can be used. Existing hard coating treatment technologies mainly include chemical immersion sealing (such as immersion in sealing solutions containing chromic acid and molybdate) and simple electrolytic hardening. However, chemical immersion sealing relies solely on physical adsorption and chemical deposition to fill pores, without a densification transformation of the main film structure. Simple electrolytic hardening typically uses the same or similar plating solutions as the coloring process, resulting in limited improvement in the corrosion resistance of the final film, and insufficient long-term stability under high humidity, salt spray, or ultraviolet radiation environments. Summary of the Invention
[0010] The technical problem to be solved by this invention is to overcome the shortcomings of existing stainless steel surface treatment technologies in forming colored oxide films with high corrosion resistance, high durability, and high color reproducibility on low-cost substrate surfaces. This invention provides a method for preparing colored oxide films that improves the corrosion resistance of stainless steel. This method can form dense colored interference oxide films on the surfaces of various types of stainless steel, such as austenitic, ferritic, and martensitic stainless steel, through a systematic electrochemical process, while taking into account low-cost mass production, controllable color, and weather resistance and durability.
[0011] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows:
[0012] A method for preparing a colored oxide film layer to improve the corrosion resistance of stainless steel, characterized by comprising the following four steps performed sequentially:
[0013] (1) Electrolytic treatment of stainless steel workpieces in sulfuric acid solution;
[0014] (2) The stainless steel workpieces that have undergone electrolytic pretreatment are placed in a plating solution containing sulfuric acid and chromic acid for electrochemical oxidation treatment;
[0015] (3) The stainless steel workpiece after oxidation coloring treatment is placed in a plating solution containing sulfuric acid and chromic acid. By controlling the thickness of the oxide film, a colored interference oxide film layer is formed on the base oxide film using the thin film interference effect of light.
[0016] (4) The stainless steel workpiece after color interference oxidation treatment is placed in a solid film solution for solid film treatment; the solid film solution contains: sulfuric acid 100–130 g / L, chromic acid 150–180 g / L, and glycerol 15–25 g / L.
[0017] Electrochemical treatment was performed using an anodic pulsed current, wherein the anodic pulsed current density was 0.3–0.8 A / dm², the pulse frequency was 0.1–1 Hz, and the duty cycle was 30–50%.
[0018] The processing temperature is 50–65℃, and the processing time is 20–30 minutes.
[0019] The above technical solution employs a multi-parameter synergistic design across four steps: electrolytic pretreatment, oxidation coloring, color interference oxidation, and electrochemical film consolidation. This constructs a complete fabrication chain encompassing pretreatment nucleation, basic growth, optical modulation, and densification reconstruction. Electrolytic pretreatment not only achieves surface cleaning but, more importantly, alters the distribution of alloying elements on the surface through electrochemical modulation. This increases the density and uniformity of subsequent oxide film nucleation sites, fundamentally improving the density and continuity of the oxide film. The oxidation coloring and color interference oxidation steps sequentially construct a bilayer synergistic structure of inner support and outer interference.
[0020] Most existing electrochemical film deposition technologies employ cathodic reduction deposition processes, physically blocking pores in the colored film layer by electrolytically depositing metallic chromium or trivalent chromium compounds. This physical filling of foreign substances not only has limited adhesion to the substrate film, but the deposit itself also alters the optical properties of the film surface, leading to interference color distortion. Furthermore, even after rapid surface blocking, deep pores remain unfilled.
[0021] This technical solution fundamentally overturns the current direction and working mechanism of existing solid film technology. It replaces traditional cathodic electrolytic deposition with anodic pulse oxidation, achieving self-thickening and densification of the oxide film's pore walls. Under the action of the anodic pulse current, the current passes through the substrate metal surface at the bottom of the oxide film pores, causing the chromium at the bottom of the pores to continue oxidizing to Cr2O3. The oxide film grows inward from the pore walls, gradually reducing the pore size. This is not the filling of foreign materials, but rather the self-thickening and densification of the oxide film itself. Because the thickened portion is homogeneous with the original film layer (Cr2O3) and has the same refractive index, it has minimal interference with optical interference effects and is chemically bonded to the substrate, resulting in a bonding force far superior to physical deposition. Glycerol forms a weak adsorption layer on the anode surface, selectively inhibiting the active dissolution sites of iron, causing the anodic oxidation reaction to preferentially occur in the chromium-rich region, promoting the uniform growth of the chromium-rich oxide film. Simultaneously, glycerol increases the solution viscosity, slowing the diffusion and loss of ions from the pores to the bulk solution during pulse power-off, maintaining a favorable chemical environment for oxide film growth within the pores. During pulse power-on, the high viscosity ensures a more uniform current distribution, avoiding over-oxidation caused by localized electric field concentration. The low-frequency pulse (0.1–1 Hz, duty cycle 30–50%) is designed based on the porous electrode mass transfer theory: the power-on phase drives pore wall oxidation and thickening, while the power-off phase allows solution ions to redistribute uniformly through diffusion, replenishing ion consumption within the pores and eliminating concentration polarization. Each cycle completes one growth and replenishment cycle, resulting in uniform thickening of the pore walls from the inside out, ultimately reducing the pore size to the nanometer scale or even closing the pores, while controlling the optical thickness variation of the film surface within 50 nm. Since the densification direction is due to the self-thickening of the pore walls rather than surface deposition, the surface geometry and optical thickness of the film are almost unaffected; simultaneously, the low current density (0.3–0.8 A / dm³) 2 The current is much lower than that of the coloring current, the oxidation rate is slow and controllable, and the pulse switching further shortens the effective oxidation time to 30-50% of the total time. Therefore, the influence of the solidification process on the interference color can be accurately predicted, and a color compensation amount can be reserved in the third process to ensure that the color of the final product meets the standard.
[0022] More preferably, the sulfuric acid solution in the electrolytic pretreatment step also contains 5–20 g / L of citric acid.
[0023] In existing technologies, the sulfuric acid solution in the electrolytic pretreatment step only serves a cleaning and coarse activation function, without fully considering the matching relationship between the degree of surface chromium enrichment and the subsequent oxide film growth requirements. This technical solution introduces citric acid as an additive into the electrolytic pretreatment solution, utilizing the multiple effects of citric acid to simultaneously improve surface uniformity and corrosion resistance.
[0024] Citric acid, as an organic acid, can react with Fe dissolved during electrolysis. 2+ Fe 3+ The ions form stable complexes, preventing redeposition of these metal ions on the stainless steel surface or the formation of uneven corrosion products. This complexation allows for a more uniform and thorough dissolution of iron and iron oxides, while chromium and chromium oxides remain relatively intact, resulting in a more uniform chromium-rich surface over a larger area. This uniform chromium-rich surface provides consistent Cr₂O₃ nucleation sites for subsequent oxidation and coloring steps, leading to a more uniform and dense growth of the base oxide film. This fundamentally improves the structural integrity of the film and lays the foundation for the uniform growth of the color interference film, significantly enhancing batch-to-batch color consistency.
[0025] Meanwhile, the selective dissolution reaction of citric acid with the stainless steel surface further enhances the enrichment of surface elements, resulting in a denser and more stable chromium-rich passivation film. This chromium-rich surface not only improves its own corrosion resistance but also provides a higher-quality growth substrate for the subsequent oxide film, resulting in stronger adhesion between the final colored oxide film and the substrate, and further improving the overall corrosion resistance of the film.
[0026] More preferably, in the electrolytic pretreatment step, the concentration of the sulfuric acid solution is 10–20% (mass percentage), and the current density is 1.0–2.0 A / dm³. 2 The processing temperature is from room temperature to 40°C, and the processing time is 8–15 minutes.
[0027] More preferably, in the oxidation coloring step, differentiated plating solution ratios and process parameters are adopted according to the microstructure and alloy composition differences of the stainless steel:
[0028] For austenitic stainless steels with a nickel content of less than 1% and a manganese content of more than 5%, the concentration of sulfuric acid in the plating bath is 140–160 g / L, the concentration of chromic acid is 190–210 g / L, the treatment temperature is 75–85℃, and the potential control range is 700–1000mV; for example, 201 stainless steel.
[0029] For austenitic stainless steels with a nickel content higher than 5% and a chromium content higher than 17%, the sulfuric acid concentration in the plating bath is 190–210 g / L, the chromic acid concentration is 170–190 g / L, the treatment temperature is 65–75℃, and the potential control range is 400–800 mV; for example, 304 stainless steel.
[0030] For ferritic stainless steel, the sulfuric acid concentration in the plating bath is 190–210 g / L, the chromic acid concentration is 170–190 g / L, the treatment temperature is 65–75℃, and the potential control range is 400–800 mV. For example, 430 stainless steel.
[0031] More preferably, in the color interference oxidation step, the concentration of sulfuric acid in the plating solution is 170–190 g / L and the concentration of chromic acid is 210–230 g / L. Through temperature-time-potential coordinated control, a color interference oxide film layer with a thickness of 200–400 nm is formed on the base oxide film. The color change process is blue, golden yellow, red, purplish red, emerald green and blue-green in sequence as the film thickness increases.
[0032] More preferably, the stainless steel workpiece includes at least one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, duplex stainless steel, or precipitation-hardening stainless steel.
[0033] Compared with the prior art, the beneficial effects of the present invention are:
[0034] This invention overcomes the shortcomings of existing stainless steel surface treatment technologies in forming high corrosion resistance, high durability, and high color reproducibility colored oxide film layers on low-cost substrates. It can form dense colored interference oxide film layers on the surfaces of various types of stainless steel, such as austenitic, ferritic, and martensitic stainless steel, through a systematic electrochemical process, while taking into account mass production at low cost, color controllability, and weather resistance and durability. Detailed Implementation
[0035] To enable those skilled in the art to better understand the technical solutions in this application, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this application.
[0036] Example 1
[0037] This embodiment provides a method for preparing a colored oxide film layer to improve the corrosion resistance of stainless steel. The substrate is a 201 stainless steel cold-rolled sheet with dimensions of 300 mm × 200 mm × 1 mm and the target color is blue.
[0038] Step (1) Electrolytic pretreatment:
[0039] A 201 stainless steel plate is vertically suspended in a special fixture and placed in an electrolytic pretreatment solution containing 15% sulfuric acid (approximately 150 g / L by mass) and 10 g / L citric acid. The stainless steel plate is used as the anode, and a lead plate as the cathode, with a current density of 1.5 A / dm³. 2 The temperature was set at room temperature (approximately 25°C) for 10 minutes. After treatment, the sample was rinsed with deionized water for 2 minutes.
[0040] Step (2) Oxidative coloring:
[0041] The pre-treated 201 stainless steel plate was placed in an anodizing and coloring plating solution composed of 150 g / L sulfuric acid and 200 g / L chromic acid. The temperature was 80℃, and a potential control method was used, controlling the potential range between 700 and 1000 mV. When the potential reached the target value (850 mV in this embodiment), the process proceeded to the next step. After treatment, the plate was rinsed with deionized water for 2 minutes.
[0042] Step (3) Color interference oxidation:
[0043] The anodized 201 stainless steel plate was placed in a colored interference anodizing solution, composed of 180 g / L sulfuric acid and 220 g / L chromic acid. The temperature was 75℃, and a temperature-time-potential synergistic control method was used. The target film thickness corresponded to the blue interference color (approximately 280 nm). When the potential reached the target range, the process proceeded to the next step. After treatment, the plate was rinsed with deionized water for 2 min.
[0044] Step (4) Electrochemical film formation:
[0045] A 201 stainless steel plate, after color interference oxidation, was placed in a solid film solution with the following composition: sulfuric acid 120 g / L, chromic acid 160 g / L, and glycerol 20 g / L. The temperature was 55℃, and anolytical pulse current treatment was applied with an anolytical pulse current density of 0.5 A / dm³. 2 The pulse frequency was 0.5 Hz, the duty cycle was 40% (power on for 0.8 s, power off for 1.2 s), and the treatment time was 25 min. After treatment, the sample was rinsed with deionized water at 60℃ for 3 min to remove residual glycerol, and then dried in a hot air drying oven at 60℃ for 15 min. A PE protective film was then applied to the surface.
[0046] Example 2
[0047] This embodiment uses 304 stainless steel cold-rolled sheet as the base material, with dimensions of 300 mm × 200 mm × 1 mm, and the target color is golden yellow.
[0048] Step (1) Electrolytic pretreatment:
[0049] The electrolytic pretreatment solution contains: 15% sulfuric acid and 10 g / L citric acid. A stainless steel plate is used as the anode, a lead plate as the cathode, and the current density is 1.5 A / dm³. 2 At room temperature, the treatment time was 10 minutes.
[0050] Step (2) Oxidative coloring:
[0051] Plating solution composition: sulfuric acid 200 g / L, chromic acid 180 g / L. Temperature 70℃, potential control range 400–800 mV (vs. SCE), target potential 600 mV.
[0052] Step (3) Color interference oxidation:
[0053] The plating solution consisted of 180 g / L sulfuric acid and 220 g / L chromic acid. The temperature was 70℃, and the target film thickness corresponded to a golden yellow interference color (approximately 350 nm).
[0054] Step (4) Electrochemical film formation:
[0055] Solid film solution composition: sulfuric acid 120 g / L, chromic acid 160 g / L, glycerol 20 g / L. Temperature 55℃, anolyte pulse current density 0.5 A / dm³. 2 The treatment was carried out at a frequency of 0.5 Hz, a duty cycle of 40%, and a processing time of 25 min. After treatment, the sample was rinsed in deionized water at 60℃ for 3 min to remove residual glycerol, and then dried in a hot air drying oven at 60℃ for 15 min. Finally, a PE protective film was applied to the surface.
[0056] Example 3
[0057] In this embodiment, 430 stainless steel cold-rolled sheet is used as the base material, with dimensions of 300 mm × 200 mm × 1 mm, and the target color is red.
[0058] Step (1) Electrolytic pretreatment:
[0059] The electrolytic pretreatment solution contains: 15% sulfuric acid and 10 g / L citric acid. A stainless steel plate is used as the anode, a lead plate as the cathode, and the current density is 1.5 A / dm³. 2 At room temperature, the treatment time was 10 minutes.
[0060] Step (2) Oxidative coloring:
[0061] Plating solution composition: sulfuric acid 200 g / L, chromic acid 180 g / L. Temperature 70℃, potential control range 400–800 mV (vs. SCE), target potential 550 mV.
[0062] Step (3) Color interference oxidation:
[0063] The plating solution consisted of 180 g / L sulfuric acid and 220 g / L chromic acid. The temperature was 70℃, and the target film thickness corresponded to the red interference color (approximately 380 nm).
[0064] Step (4) Electrochemical film formation:
[0065] The solidification solution consisted of 120 g / L sulfuric acid, 160 g / L chromic acid, and 20 g / L glycerol. The temperature was 55℃, the anolyte pulse current density was 0.5 A / dm², the frequency was 0.5 Hz, the duty cycle was 40%, and the treatment time was 25 min. After treatment, the sample was rinsed with deionized water at 60℃ for 3 min to remove residual glycerol, and then dried in a hot air drying oven at 60℃ for 15 min. Finally, a PE protective film was applied to the surface.
[0066] Example 4
[0067] In this embodiment, 304 stainless steel cold-rolled sheet is used as the base material, and the target color is emerald green.
[0068] Step (1) Electrolytic pretreatment:
[0069] Same as Example 2.
[0070] Step (2) Oxidative coloring:
[0071] Same as Example 2.
[0072] Step (3) Color interference oxidation:
[0073] The plating bath composition was 180 g / L sulfuric acid and 220 g / L chromic acid. Temperature control was as follows: 80℃ for the initial rapid growth stage, 75℃ for the mid-term stable growth stage, and 70℃ for the later precise control stage. The target film thickness corresponded to a bright green interference color (approximately 420 nm). The film was immediately transferred to the solidification step when the potential reached the target range.
[0074] Step (4) Electrochemical film formation:
[0075] Same as Example 2.
[0076] Comparative Example 1
[0077] This comparative example uses the traditional INCO process, referring to existing technology. The substrate is 304 stainless steel cold-rolled sheet, with dimensions of 300mm × 200mm × 1mm.
[0078] Step (1) Preprocessing:
[0079] Immerse the 304 stainless steel sheet in an alkaline degreasing solution (30 g / L sodium hydroxide, 20 g / L sodium carbonate, 5 g / L surfactant, 60℃) for 10 min to remove surface oil; then rinse with deionized water for 2 min. Next, immerse the degreased stainless steel sheet in an acid pickling activation solution (10% sulfuric acid, room temperature) for 3 min to remove surface oxide scale; then rinse with deionized water for 2 min.
[0080] Step (2) Coloring:
[0081] The pretreated 304 stainless steel sheet was placed in a coloring solution with the following composition: CrO3 250 g / L and H2SO4 450 g / L. The temperature was 85℃, and a traditional time-controlled method was used with a fixed treatment time of 10 min; no potential monitoring was performed. After coloring, the sheet was rinsed with deionized water for 2 min.
[0082] Step (3) Solidification:
[0083] The colored 304 stainless steel plate was placed in a solidification solution, which was a 250 g / L aqueous solution of chromic acid, at room temperature (approximately 25°C). The 304 stainless steel plate was used as the cathode, and the lead plate as the anode. A cathode direct current of 1.2 A / dm³ was applied. 2 The processing time is 6 minutes. After the film is solidified, rinse with deionized water for 2 minutes, then air dry naturally, and cover the surface with a PE protective film.
[0084] Comparative Example 2
[0085] The difference between this comparative example and Example 2 is that the solid film solution does not contain glycerol.
[0086] The substrate and steps (1) to (3) are the same as in Example 2.
[0087] Step (4): The solid film solution consists of 120 g / L sulfuric acid and 160 g / L chromic acid, and does not contain glycerol. Temperature: 55℃; Anode pulse current density: 0.5 A / dm³. 2 The frequency is 0.5 Hz, the duty cycle is 40%, and the processing time is 25 min.
[0088] Performance testing
[0089] The following performance tests were performed on the samples prepared in the above embodiments and comparative examples:
[0090] (1) Corrosion resistance: The time when rust spots appeared was recorded by using a neutral salt spray test (NSS, 5% NaCl, 35℃); the polarization curve was tested by using an electrochemical workstation to obtain the corrosion potential Ecorr and corrosion current density icorr.
[0091] (2) Film hardness: The surface hardness of the film was measured using a microhardness tester (load 10 g, holding pressure 15 s).
[0092] (3) Weather resistance: The QUV accelerated aging test (UVA-340 lamp tube, 60℃ / 8 h light exposure + 50℃ / 4 h condensation cycle) was used to record the color change ΔE and gloss retention rate of the film.
[0093] (4) Bending test: Bend the sample 90° (shaft diameter equal to plate thickness) and observe whether the film layer cracks or peels off.
[0094] The test results are shown in Table 1.
[0095] Table 1. Test results of each embodiment and comparative example.
[0096]
[0097] Table 1 shows that Example 1 (201 stainless steel), Example 2, Example 4 (304 stainless steel), and Example 3 (430 stainless steel) respectively covered austenitic low corrosion resistant grades, austenitic high corrosion resistant grades, and ferritic stainless steel. The salt spray test times for the three reached 1680 h, 1920 h, and 1550 h, respectively, and no cracking or peeling was observed in the bending test. This indicates that the four-step integrated synergistic process of the present invention can effectively adapt to stainless steels with different microstructures, forming a corrosion resistance level close to that of the high corrosion resistant grade (304) on the surface of the low corrosion resistant grades (201, 430), truly achieving the technical goal of replacing high corrosion resistant stainless steel with low-cost stainless steel.
[0098] The salt spray test time for Example 2 was 1920 h, while that for Comparative Example 1 was only 720 h. The corrosion potential of Example 2 was much higher than that of Comparative Example 1, and the film hardness was also significantly higher. The color difference ΔE after QUV aging in Example 2 was 0.72, while that in Comparative Example 1 was 2.50. These results indicate that the process of the present invention comprehensively surpasses the traditional INCO method in overall performance.
[0099] The salt spray test time of Comparative Example 2 was 1420 h, which was shorter than that of Example 2 (1920 h), indicating that anodic pulse oxidation itself has a film-fixing effect, but the introduction of glycerol has significantly improved this effect.
[0100] Example 5
[0101] In this embodiment, 201 stainless steel cold-rolled sheet is used as the base material, and the target color is purplish-red.
[0102] Five pieces of 201 stainless steel sheet from the same batch were cut into five pieces (numbered 5-1 to 5-5), and each piece was processed according to steps (1) and (2) of Example 1. In step (3) color interference oxidation, the target film thickness corresponds to purplish-red (approximately 400 nm).
[0103] Potential control method group (5-1 to 5-3):
[0104] A potential control method was used, with the potential range controlled between 700 and 1000 mV. The reaction was terminated immediately when the potential reached 950 mV. The actual processing time for each workpiece was recorded.
[0105] Time control method group (5-4 to 5-5):
[0106] The traditional time control method was used, with the treatment time fixed as the average time of the potential control group (approximately 8.5 min), and the potential was not monitored.
[0107] After all workpieces undergo electrochemical film formation in step (4), color parameters (Lab*) are measured using a colorimeter, and the color difference ΔE within the batch is calculated. The results are shown in Table 2.
[0108] Table 2 Color difference values of workpieces obtained by different control methods
[0109]
[0110] The results showed that the intra-batch color difference ΔE of the potential control method groups (5-1 to 5-3) were 0.65, 0.70, and 0.68, respectively, with an average of 0.68, which is far below the industrially acceptable threshold (ΔE < 1.5). The intra-batch color difference ΔE of the time control method groups (5-4 to 5-5) were 2.85 and 3.20, respectively, significantly higher than those of the potential control method group. These results indicate that the potential control method directly reflects the actual growth state of the oxide film and has significantly stronger robustness to process disturbances such as solution temperature fluctuations and concentration changes, effectively solving the technical problem of poor batch color consistency in industrial mass production.
[0111] Example 6
[0112] This embodiment uses 304 stainless steel cold-rolled sheet as the substrate, with a target color of golden yellow, to verify the role of citric acid in the electrolytic pretreatment solution.
[0113] Ten pieces of 304 stainless steel sheet from the same batch were cut and processed according to steps (2) to (4) of Example 2. The difference is:
[0114] Steps 6-1 to 6-5: (1) The electrolytic pretreatment solution contains: 15% sulfuric acid (approximately 150 g / L) and 10 g / L citric acid. Current density: 1.5 A / dm³ 2At room temperature, the treatment time was 10 minutes.
[0115] 6-6 to 6-10:
[0116] Step (1) The electrolytic pretreatment solution contains 15% sulfuric acid (approximately 150 g / L) and does not contain citric acid. The remaining parameters are the same as in 6-1 to 6-5.
[0117] The relevant properties of the workpiece samples were tested. The average values of five samples were used for treatment groups 6-1 to 6-5, and the average values of five samples were used for treatment groups 6-6 to 6-10. The results are shown in Table 3.
[0118] Table 3
[0119]
[0120] The results showed that the salt spray test duration for treatment groups 6-1 to 6-5 was 1920 h, while that for treatment groups 6-6 to 6-10 was only 1580 h; the corrosion potential of the former (+220 mV) was significantly higher than that of the latter (+175 mV), and the corrosion current density (0.18 μA / cm²) was also significantly higher. 2 The value was significantly lower than the latter (0.32 μA / cm). 2 The film hardness (HV 850) of the former (HV 780) is higher than that of the latter, and the color difference ΔE after QUV aging is 0.72, while that of the latter is 1.15. These results indicate that citric acid in the electrolytic pretreatment solution reacts with Fe... 2+ / Fe 3+ The formation of stable complexes prevents the redeposition of metal ions, resulting in a more uniform and thorough dissolution of iron and iron oxides, while chromium and chromium oxides remain relatively intact. This allows for uniform chromium enrichment of the surface over a larger area. The uniform chromium-rich surface provides consistent Cr2O3 nucleation sites for subsequent oxidation and coloring steps, leading to a more uniform and dense growth of the base oxide film. This fundamentally improves the structural integrity of the film and significantly enhances batch-to-batch color consistency and overall corrosion resistance.
Claims
1. A method for preparing a colored oxide film layer to improve the corrosion resistance of stainless steel, characterized in that, It includes the following four steps performed in sequence: (1) Electrolytic pretreatment step: The stainless steel workpiece is placed in a sulfuric acid solution for electrolytic treatment; (2) Oxidation coloring step: The stainless steel workpiece after electrolytic pretreatment is placed in a plating solution containing sulfuric acid and chromic acid for electrochemical oxidation treatment; (3) Color interference oxidation step: The stainless steel workpiece after oxidation coloring treatment is placed in a plating solution containing sulfuric acid and chromic acid to form a color interference oxide film layer on the base oxide film; (4) Electrochemical film-forming step: The stainless steel workpiece after color interference oxidation treatment is placed in a film-forming solution for film-forming treatment; the film-forming solution contains: sulfuric acid 100–130 g / L, chromic acid 150–180 g / L, and glycerol 15–25 g / L; electrochemical treatment is performed using an anodic pulse current, wherein: the anodic pulse current density is 0.3–0.8 A / dm 2 The pulse frequency is 0.1–1 Hz, the duty cycle is 30–50%, the processing temperature is 50–65℃, and the processing time is 20–30 minutes.
2. The preparation method according to claim 1, characterized in that, The sulfuric acid solution in the electrolytic pretreatment step also contains 5–20 g / L of citric acid.
3. The preparation method according to claim 1, characterized in that, In the electrolytic pretreatment step, the mass concentration of the sulfuric acid solution is 10–20%, and the current density is 1.0–2.0 A / dm³. 2 The processing temperature is from room temperature to 40°C, and the processing time is 8–15 minutes.
4. The preparation method according to claim 1, characterized in that, In the oxidation coloring step, for austenitic stainless steel with a nickel content of less than 1% and a manganese content of more than 5%, the concentration of sulfuric acid in the plating solution is 140–160 g / L, the concentration of chromic acid is 190–210 g / L, the treatment temperature is 75–85℃, and the potential control range is 700–1000 mV.
5. The preparation method according to claim 1, characterized in that, In the oxidation coloring step, for austenitic stainless steel with a nickel content higher than 5% and a chromium content higher than 17%, the concentration of sulfuric acid in the plating solution is 190–210 g / L, the concentration of chromic acid is 170–190 g / L, the treatment temperature is 65–75℃, and the potential control range is 400–800 mV.
6. The preparation method according to claim 1, characterized in that, In the oxidation coloring step, for ferritic stainless steel, the concentration of sulfuric acid in the plating solution is 190–210 g / L, the concentration of chromic acid is 170–190 g / L, the treatment temperature is 65–75℃, and the potential control range is 400–800 mV.
7. The preparation method according to claim 1, characterized in that, In the color interference oxidation step, the concentration of sulfuric acid in the plating solution is 170–190 g / L and the concentration of chromic acid is 210–230 g / L.
8. The preparation method according to claim 1, characterized in that, The solid film solution contains: 120 g / L sulfuric acid, 160 g / L chromic acid, and 20 g / L glycerol; the anolyte pulse current density is 0.5 A / dm³. 2 The pulse frequency was 0.5 Hz, the duty cycle was 40%, the processing temperature was 55℃, and the processing time was 25 minutes.
9. The preparation method according to claim 6, characterized in that, In the electrolytic pretreatment step, the sulfuric acid solution concentration is 15% (mass percentage), the citric acid content is 10 g / L, and the current density is 1.5 A / dm³. 2 Treat at room temperature for 10 minutes.
10. The preparation method according to any one of claims 1-9, characterized in that, The stainless steel workpiece includes at least one of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, duplex stainless steel, or precipitation hardening stainless steel.
